Critical coarctation of the aorta in newborn - A case presentation - Żybowska, Monika; Rzewuska, Anna; Sielwanowska, Wiktoria; Syzdoł, Bartłomiej; Woźniak, Magdalena (Journal of Education, Health and Sport, 2022)
Background: Heart defects are the most popular congenital disease noticed among infants. Aortic Coarctation (CoA) forms 5 - 10 % of congenital heart diseases. The heart defect consist on aortic coarctation between inlet of the left subclavian artery and origin of the arterial ligament. In the during neonatal and early infantile period, in case of delayed diagnosis, it may lead to acute heart failure and the death of the child. Case report: A female infant born at 37 weeks of gestation, by caesarean section, in good condition, was admitted to the Neonatal Department. There was a suspicion of CoA in the fetus in the pregnancy history. The Echocardiography showed a narrowing of the carpal tunel, prostin was included in the treatment. In the second day of life, the child was transferred to the Cardiology Department. Four-extremity blood pressures test showed higher values in the upper limbs than in the lower limbs. Echocardiography revealed hypoplasia of the aortic arch in the section below the exit of the second cephalic vessel with coarctation at the isthmus site. Laboratory tests showed a high level of pro-BNP. The control echocardiography showed the anatomy of the defect as before, an unobstructed wide arterial duct with a dominant R-L flow, a flow in the descending aorta of 2.7 m/s, with a coartable flow spectrum. The child was transported to the Department of Cardiac Surgery, Heart Transplantation and Mechanical Circulatory Support for Children in Zabrze for surgical treatment. Conclusions: In neonates and infants with critical aortic stenosis, ensure the patency of the ductus arteriosus with continuous intravenous infusion of prostaglandin E1. Currently, echocardiography is the basic method in the diagnosis of aortic stenosis.